Optimizing Pulmonary Rehabilitation in Chronic Obstructive Pulmonary Disease – Practical Issues: A Canadian Thoracic Society Clinical Practice Guideline - Darcy D Marciniuk; Dina Brooks; Scott Butcher; Richard Debigare; Gail Dechman; Gordon Ford; Veronique Pepin; Darlene Reid; Andrew W Sheel; Micheal K Stickland; David C Todd; Shannon L Walker; et al. (Canadian Respiratory Journal)
Pulmonary rehabilitation (PR) participation is the standard of care for patients with chronic obstructive pulmonary disease (COPD) who remain symptomatic despite bronchodilator therapies. However, there are questions about specific aspects of PR programming including optimal site of rehabilitation delivery, components of rehabilitation programming, duration of rehabilitation, target populations and timing of rehabilitation. The present document was compiled to specifically address these important clinical issues, using an evidence-based, systematic review process led by a representative interprofessional panel of experts.